Users' perceptions on internet financial reporting - Dolinšek, Tatjana (Organizacija (Kranj), 2014)
Background and Purpose: The objective of this research was to explore the perceptions of the users regarding Internet financial reporting practices in Slovenia. With this research, we wanted to determine what the perceptions of the users are regarding the reliability, credibility, usefulness and sufficiency of online accounting information and how their expectations regarding the content of accounting information differ from the actual situation. Design/ Methodology/ Approach: This research has two parts: in the first part, we summarised the actual situation regarding publishing of internet financial reporting on a sample of large companies in Slovenia (n=110) while, in the second part, we conducted a survey with which we assessed the expectations of users as regards of accounting information (n=127). We then compared users' expectations with the actual situation, analysed by evaluation of 110 websites of Slovene companies. Results: In the research we found that 52.6% of companies publish their accounting information on their websites and that on average 40.2% of users actually make use of this information We found that users have evaluated all four of characteristics: reliability, credibility, usefulness and sufficiency above average, whereby they evaluated usefulness with the highest grade and sufficiency with the lowest. Conclusion: The results of this research can offer companies a feedback on users´ expectations, particularly in cases where these expectations are greater than the actual situation. We have determined that users generally want information that indicates the financial status of a company (such as the Rating Report and data on the company's liquidity), as these information are currently expected by users but available information do not meet their need in full.
Keywords: podjetja; poslovne finance; računovodske informacije; računovodski izkazi; elektronski mediji; internet (računalniško omrežje)